Eksplorasi Persepsi Mahasiswa Kota Kupang terhadap Kualitas Produk dan Citra Merek dalam Membentuk Keputusan Pembelian Brand Fashion Lokal - Andi Detia; Pebriansyah Pebriansyah (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This research is motivated by the increasing consumer interest in local fashion products, which are able to compete with global brands. However, there are still doubts about the consistency of quality and brand image. The purpose of this study is to explore the perceptions of Kupang City students regarding the product quality and brand image of local fashion brands, and how both influence student consumer purchasing decisions. This study uses a descriptive qualitative approach with data collection conducted through in-depth interviews and observations. Informants were selected using a purposive sampling technique, involving five active students in Kupang City. The results show that product quality is a major factor in influencing Kupang City students' purchasing decisions towards local fashion brands, with a focus on aspects of material, comfort, and durability. Furthermore, brand image plays a role in forming initial perceptions and is a driving factor in purchasing interest, but its influence is highly dependent on consistent product quality. Digital media such as Instagram and TikTok serve as the main means in shaping brand image through social proof. This study also shows a shift in Kupang City students' consumption behavior from a hedonistic orientation to quality-based purchasing